THE EFFECT OF EXPERIENTIAL MARKETING AND RETAIL MARKETING MIX ON CONSUMER LOYALTY THROUGH CUSTOMER SATISFACTION AS A MEDIATION VARIABLE IN THE SANJAI DUNSANAK KITO’S FOOD SOUVENIR SHOP - Fernanda, Renol; Syafrizal, Syafrizal (Buletin Studi Ekonomi, 2019)
Abstract: The Effect of Experiential Marketing and Retail Marketing Mix on Consumer Loyalty Through Customer Satisfaction as a Mediation Variable in The Sanjai Dunsanak Kito’s Food Souvenir Shop. This study aims to examine: 1) the effect of experiential marketing on consumer satisfaction in the Sanjai Dunsanak Kito’s food souvenir shop 2) the effect of retail marketing mix on consumer satisfaction in the Sanjai Dunsanak Kito's food souvenir shop 3) the effect of customer satisfaction on consumer loyalty in the Sanjai Dunsanak Kito’s food souvenir shop 4) the effect of experiential marketing on consumer loyalty in the Sanjai Dunsanak Kito's food souvenir shop 5) the effect of retail marketing mix on consumer loyalty in the Sanjai Dunsanak Kito's food souvenir shop 6) the effect of experiential marketing on consumer loyalty through customer satisfaction as mediation variable in the Sanjai Dunsanak Kito’s food souvenir shop 7) the effect of retail marketing mix on consumer loyalty through customer satisfaction as a mediating variable in the Sanjai Dunsanak Kito’s food souvenir shop. The object of the research is the food souvenir shop Sanjai Dunsanak Kito. Keywords: Experiential Marketing, Retail Marketing Mix, Customer Satisfaction and Customer Loyalty.